Valuing the synergy in the water-energy-food nexus for cropping systems: a case in the North China Plain. (August 2021) - Li, Jinna; Cui, Jixiao; Sui, Peng; Yue, Shunnian; Yang, Jia; Lv, Ziqing; Wang, Dong; Chen, Xingqiong; Sun, Beibei; Ran, Mengmeng; Chen, Yuanquan
Highlights: A water-energy-food relative index for cropping systems at the field scale is proposed. Synergy among water, energy and food in the North China Plain is evaluated. Sustainable systems can balance crop production while reducing resource depletion. Abstract: Extreme climate change, rapid population growth and economic development drive a growing demand for resources, which lead to energy, food, water and their intertwined nexus becoming increasingly important. Agricultural decisions considering the interconnections among water, energy, and food are critical. The consumption of large amounts groundwater and non-renewable energy by the predominant traditional wheat-maize cropping system has caused a serious water shortage in the North China Plain (NCP), which is a large food production region in China. This situation has strained the relationship between water/energy consumption and food production. It is important to seek synergy in the water-energy-food nexus. This paper proposed a relative index of water-energy-food ( WEFRI ) based on different values of resource consumption and use efficiency between treatment systems and control system to analyze the synergy between water utilization, energy consumption and food supply in different cropping systems at the field scale. The goal is to seek a sustainable cropping system to balance crop production while reducing energy consumption and water depletion. In this case, different systems including monocropped maize ( Zea mays ) (MM), intercropped maize and soybean ( Glycine max) (MS), relay cropped of maize with pea ( Pisum sativum ) (MP) and potato ( Solanum tuberosum ) (MO), rotation of maize with spinach ( Spinacia oleracea ) (MI) and ryegrass ( Secale cereale ) (MR), and using traditional wheat-maize ( Triticum aestivum ) (MW) as a control. MM, MS, MP and MO were the best systems within a particular range of food supply reduction. The WEFRI of the MM/MS system was the highest (2.96/2.78). Compared to the MW system, the groundwater consumption of MM/MS was reduced by 73.84%/73.84%, and non-renewable energy inputs were reduced by 48.01%/48.30%; however, the food supply decreased by 48.05%/51.70%. The WEFRI of the MP system was 1.98. In comparison with the MW system, the groundwater consumption of the MP system was reduced by 28.46%, and the non-renewable energy inputs were reduced by 42.68%. However, the food supply decreased by 37.13%. The WEFRI of MO system was 1.92. Compared to the MW system, the groundwater consumption of MO was reduced by 11.47%, non-renewable energy inputs were reduced by 32.14%, and the food supply only decreased by 26.27%. In conclusion, we theoretically proposed the following references for cropping systems in the NCP: MM and MS are implemented when the areas has extreme water shortages, MO is implemented when a less than 30% reduction in the food supply capacity is acceptable, and MP is recommended if a 30%–40% reduction in the food supply is acceptable.